Problems and Countermeasures of the Integration of Information Technology and English Curriculum in Secondary Vocational Schools - Li, Congcong (Journal of Education and Educational Technologies, 2023)
With the development of information technology, information teaching has become an important teaching method. The theory and practice of information-based teaching have become increasingly rich, and the technical means have become increasingly diversified. At present, the focus of the research has shifted from focusing on the construction of hardware, software and resources to focusing on the effectiveness of the application of information technology in schools and classrooms, that is, the effect, efficiency and efficiency of information teaching. This paper gives some opinions on how to realize the effective integration of information technology and secondary vocational English curriculum and the corresponding countermeasures.